2016
DOI: 10.1002/alr.21737
|View full text |Cite
|
Sign up to set email alerts
|

Wraparound eyeglasses improve symptoms and quality of life in patients with seasonal allergic rhinoconjunctivitis

Abstract: Standard wraparound eyeglasses can provide a safe, convenient, and effective measure for protection from pollens in patients with SAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Allergic rhinitis (AR) is a symptomatic nose inflammation caused by immunoglobulin E (IgE)-mediated endocardial inflammation (Bousquet et al, 2008). AR is one of the most common chronic diseases in the world, influencing 10 to 20% of the population (Devillier et al, 2014;Comert et al, 2016). Pollen is the biggest reported reason of seasonal allergic rhinoconjunctivitis (SAR) (Caillaud et al, 2015).…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…Allergic rhinitis (AR) is a symptomatic nose inflammation caused by immunoglobulin E (IgE)-mediated endocardial inflammation (Bousquet et al, 2008). AR is one of the most common chronic diseases in the world, influencing 10 to 20% of the population (Devillier et al, 2014;Comert et al, 2016). Pollen is the biggest reported reason of seasonal allergic rhinoconjunctivitis (SAR) (Caillaud et al, 2015).…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…There was no significant difference between intervention and control group in nasal symptoms (p = .256). Comert et al 46 = −1.10, p = .02. 46 Additionally, there was a statistically significant reduction of sneezing, rhinorrhea, and an improvement in QoL.…”
Section: Randomized Studies Cochrane Collaboration's Tool For Assessing Risk Of Bias In Randomized Trialsmentioning
confidence: 86%
“…The study supports the hypothesis that face masks may reduce the symptoms of allergic rhinitis [ 15 ]. Another study investigated the efficacy of wearing eyeglasses showed that it was effective in controlling symptoms, improving the quality of life, and reducing the need for medicine in patients with seasonal allerjic rhinitis [ 16 ]. In our study, we evaluated the protective effect of spending less time outdoors, wearing a face mask, and taking a shower on return home in patients with seasonal allergic rhinitis and asthma.…”
Section: Discussionmentioning
confidence: 99%